The mass discrepancy acceleration relation in early-type galaxies: extended mass profiles and the phantom menace to MOND - Janz, J; Cappellari, M; Romanowsky, A; Ciotti, L; Alabi, A; Forbes, D (Oxford University Press, 2016)
The dark matter (DM) haloes around spiral galaxies appear to conspire with their baryonic content: empirically, significant amounts of DM are inferred only below a universal characteristic acceleration scale. Moreover, the discrepancy between the baryonic and dynamical mass, which is usually interpreted as the presence of DM, follows a very tight mass discrepancy acceleration (MDA) relation. Its universality, and its tightness in spiral galaxies, poses a challenge for the DM interpretation and was used to argue in favour of MOdified Newtonian Dynamics (MOND). Here, we test whether or not this applies to early-type galaxies. We use the dynamical models of fast-rotator early-type galaxies by Cappellari et al. based on ATLAS 3D and SAGES Legacy Unifying Globulars and GalaxieS (SLUGGS) data, which was the first homogenous study of this kind, reaching ∼4Re, where DM begins to dominate the total mass budget. We find the early-type galaxies to follow an MDA relation similar to spiral galaxies, but systematically offset. Also, while the slopes of the mass density profiles inferred from galaxy dynamics show consistency with those expected from their stellar content assuming MOND, some profiles of individual galaxies show discrepancies.